2017
DOI: 10.1111/apha.12932
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of integrin α11 induces cardiac fibrosis in mice

Abstract: We report for the first time that overexpression of integrin α11 induces cardiac fibrosis and left ventricular hypertrophy. This is a result of changes in intracellular hypertrophic signalling and secretion of soluble factors that increase collagen production in the heart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 39 publications
4
28
0
Order By: Relevance
“…The reduction effect was dramatically enhanced when CMs were pretreated with these two antibodies at the same time. These data indicated that CMs interact with CN through α 10 ‐ and α 11 ‐integrin, consistent with previous studies that α 10 ‐ and α 11 ‐integrin are collagen‐binding receptors on cells . Mean force and binding probability reduced significantly when CMs pretreated with anti‐α 3 ‐, ‐α 5 ‐integrin antibodies or both interacted with FN.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…The reduction effect was dramatically enhanced when CMs were pretreated with these two antibodies at the same time. These data indicated that CMs interact with CN through α 10 ‐ and α 11 ‐integrin, consistent with previous studies that α 10 ‐ and α 11 ‐integrin are collagen‐binding receptors on cells . Mean force and binding probability reduced significantly when CMs pretreated with anti‐α 3 ‐, ‐α 5 ‐integrin antibodies or both interacted with FN.…”
Section: Resultssupporting
confidence: 91%
“…The CN, FN, and LN are three ECM proteins binding to different integrins, corresponding to different physiological functions . The data in the present study showed that the unbinding force of LN‐CM integrins has the greatest value, whereas FN‐CM integrins have the smallest under the same loading rate (Figure 2).…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…1 Another group of MR techniques for tissue characterization makes use of the relaxation time T 2 to probe for tissue water changes or the apparent water diffusion coefficient (ADC) to monitor changes in the intra-and extracellular volume. The capabilities of parametric MRI using the MR relaxation parameter T 1 for non-invasive tissue characterization were employed to demonstrate that overexpression of integrin α11 induces cardiac fibrosis and left ventricular hypertrophy in mice.…”
Section: Rich Opportunities For Discoverymentioning
confidence: 99%